Comparing the Catalytic and Structural Characteristics of a 'Short' Unspecific Peroxygenase (UPO) Expressed in Pichia pastoris and Escherichia coli. (30th November 2022) - Robinson, Wendy X. Q.; Mielke, Tamara; Melling, Benjamin; Cuetos, Anibal; Parkin, Alison; Unsworth, William P.; Cartwright, Jared; Grogan, Gideon
Abstract: Unspecific peroxygenases (UPOs) have emerged as valuable tools for the oxygenation of non‐activated carbon atoms, as they exhibit high turnovers, good stability and depend only on hydrogen peroxide as the external oxidant for activity. However, the isolation of UPOs from their natural fungal sources remains a barrier to wider application. We have cloned the gene encoding an 'artificial' peroxygenase (artUPO), close in sequence to the 'short' UPO from Marasmius rotula ( Mro UPO), and expressed it in both the yeast Pichia pastoris and E. coli to compare the catalytic and structural characteristics of the enzymes produced in each system. Catalytic efficiency for the UPO substrate 5‐nitro‐1, 3‐benzodioxole (NBD) was largely the same for both enzymes, and the structures also revealed few differences apart from the expected glycosylation of the yeast enzyme. However, the glycosylated enzyme displayed greater stability, as determined by nano differential scanning fluorimetry (nano‐DSF) measurements. Interestingly, while artUPO hydroxylated ethylbenzene derivatives to give the ( R )‐alcohols, also given by a variant of the 'long' UPO from Agrocybe aegerita ( Aae UPO), it gave the opposite ( S )‐series of sulfoxide products from a range of sulfide substrates, broadening the scope for application of the enzymes. The structures of artUPO reveal substantial differences to that of Aae UPO, and provide a platform for investigating the distinctive activity of this and related'short' UPOs. Abstract : Unspecific peroxygenases (UPOs) are valuable tools for the oxygenation of non‐activated carbon atoms, as they exhibit high turnovers, good stability and depend only on hydrogen peroxide as the external oxidant for activity. We have cloned the gene encoding an 'artificial' peroxygenase (artUPO), close in sequence to the 'short' UPO from Marasmius rotula ( Mro UPO), and expressed it in both the yeast Pichia pastoris and E. coli to compare the catalytic and structural characteristics of the enzymes produced in each system.